Utilization study of antidiabetic agents in a teaching hospital of Sikkim and adherence to current standard treatment guidelines - Sushrut Varun Satpathy; Supratim Datta; Binu Upreti (Wolters Kluwer Medknow Publications, 2016)
Objective: Diabetes has gradually emerged as one of the most serious public health problems in our country. This underlines the need for timely disease detection and decisive therapeutic intervention. This prospective cross-sectional observational study aims at analyzing the utilization pattern of antidiabetic agents in a remote North-East Indian tertiary care teaching hospital in the perspective of current standard treatment guidelines. Materials and Methods: Diabetic patients receiving antidiabetic medication, both as outpatients and inpatients in our hospital over a period of 12 months (May 2013-May 2014), were included in this study. The data obtained were sorted and analyzed on the basis of gender, type of therapy, and hospital setting. Results: A total of 310 patients were included in the study. Metformin was the single most frequently prescribed antidiabetic agent (66.8%) followed by the sulfonylureas group (37.4%). Insulin was prescribed in 23.2% of the patients. Combination antidiabetic drug therapy (65.1%) was used more frequently than monotherapy (34.8%). The use of biguanides (P < 0.0001) and sulfonylureas (P = 0.02) in combination was significant as compared to their use as monotherapy. A total of 48% of all antidiabetic combinations used, comprised metformin and sulfonylureas (n = 96). Insulin use was significantly higher as monotherapy and in inpatients (P< 0.0001). The utilization of drugs from the National List of Essential Medicines was 51.2%, while 11% of antidiabetics were prescribed by generic name. Conclusion: The pattern of utilization largely conforms to the current standard treatment guidelines. Increased use of generic drugs is an area with scope for improvement.